The widow's house [large type] - Goodman, Carol (Wheeler Publishing, 2017)
When Jess and Clare Martin move to their former college town in the Hudson River Valley, they are hoping for rejuvenation -- of their marriage, their savings, and Jess's writing career. But their new life as caretakers of a crumbling estate isn't all quaint town libraries and fragrant apple orchards. Something is just not right at Riven House.